Characterization of the Xerophyta humilis desiccation induced-1 (Xhdsi-1voc) gene : a member of the Vicinal Oxygen Chelate (VOC) metalloenzyme superfamily upregulated in X. humilis (BAK) DUR and SCHINZ during desiccation - Mulako, Inonge (Department of Molecular and Cell Biology, 2014)
Includes abstract.